ANALISIS PENENTUAN TARIF AIR MINUM PDAM KABUPATEN LAMONGAN BERDASARKAN PRINSIP FULL COST RECOVERY - Istichori Istichori; I Putu Artama Wiguna; Ali Masduqi (Journal of Civil Engineering, 2018)
Water supply in southern part of Lamongan Regency, i.e. Mantup District (Mantup Village), Tikung District (Takeranklating and Bakalanpule Village), and Kembangbahu District (Puter Village) will be served by PDAM from Mojolamong Regional Water Supply System. About 70% villagers in these rural area use groundwater well and others sources of water, while the rest 30% get their water from Hippam. PDAM of Lamongan Regency purchased treated water from Mojolamong Regional Water Supply System and then distribute it to the customer. One of basic principle in the determination of water tariff is full cost recovery, i.e. calculating all basic costs collected from investation, operation, and maintenance, so that the earned income can replace all cost have been spent. Study result show that water tariff rate based on full cost recovery with 9.48% of MARR generated NPV value on Rp.2,876,367,948 (NPV>0), IRR value at 10.74% (IRR≥MARR), and Payback Period through 19 years operation is determined with water tariff at Rp.3,700/m3.